2008
DOI: 10.1002/maco.200804162
|View full text |Cite
|
Sign up to set email alerts
|

SVET study of the corrosion protection of electrodeposited Zn and Zn‐Co‐Fe alloy coated steels

Abstract: The scanning vibrating electrode technique (SVET) was applied to study the corrosion resistance of partially coated (Zn and various Zn-Co-Fe alloys) and partially exposed steel samples in 10 mM NaCl solution. The sacrificial properties and the protection range decreases with increase in Co content in the alloy. For high Co content in the alloy, the coating becomes more noble to steel and loses its sacrificial protection. The barrier resistance of the coatings increases with the increase in Co content in the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A fast research of the literature indicates that in recent investigations, the SVET was applied to determine the extent of corrosion protection imparted by metallic coating on steel. Oltra et al (2007), Desphane (2010), andLodhi et al (2008) used the SVET to study the protection of several coated alloys and found that they are corrosion resistant. These works demonstrated the usefulness of the SVET technique in corrosion studies for the selection of suitable materials for industrial plants, marine infrastructure and oil and gas installations, frequently affected by localized corrosion.…”
Section: Discussionmentioning
confidence: 99%
“…A fast research of the literature indicates that in recent investigations, the SVET was applied to determine the extent of corrosion protection imparted by metallic coating on steel. Oltra et al (2007), Desphane (2010), andLodhi et al (2008) used the SVET to study the protection of several coated alloys and found that they are corrosion resistant. These works demonstrated the usefulness of the SVET technique in corrosion studies for the selection of suitable materials for industrial plants, marine infrastructure and oil and gas installations, frequently affected by localized corrosion.…”
Section: Discussionmentioning
confidence: 99%
“…This measurement is in proximity of the metal surface and the distance between the probe and metal surface is generally in about 100 mm range. This technique has been extensively used for localized corrosion research [29][30][31].…”
Section: Scanning Vibrating Electrode Technique (Svet)mentioning
confidence: 99%